The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ejn.14680
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological dissociation of the interaction between time pressure and trait anxiety during spatial orientation judgments

Abstract: Spatial orientation is achieved by integrating visual, vestibular and proprioceptive cues. Individuals that rely strongly upon visual cues to facilitate spatial orientation are termed visually dependent. Heightened visual reliance commonly occurs in patients following vestibular dysfunction and can influence clinical outcome. Additionally, psychological factors, including anxiety, are associated with poorer clinical outcome following vestibular dysfunction. Given that visual dependency measures are affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…It may therefore be beneficial in the case of continuous vestibular stimulation by vestibular implants during natural head movements. Resting state brain activity should be considered when abnormal visual–vestibular interaction is evaluated and symptoms of visual vertigo and anxiety (Bednarczuk et al, ) should be assessed and related to changes of resting state activity, potential cofactors which we did not explicitly studied here.…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be beneficial in the case of continuous vestibular stimulation by vestibular implants during natural head movements. Resting state brain activity should be considered when abnormal visual–vestibular interaction is evaluated and symptoms of visual vertigo and anxiety (Bednarczuk et al, ) should be assessed and related to changes of resting state activity, potential cofactors which we did not explicitly studied here.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean VD in the faller group was 3.4 (SD = 4.3) degrees, being less marked than in the dynamic SVV, perhaps due to a greater static SVV error in the faller group-a factor used to compute VD. We cannot differentiate whether abnormal dynamic SVV is a consequence of increased perceived fall risk, or causally related to fall risk, given the known influences of anxiety upon visual dependency, at least in young individuals (Bednarczuk et al, 2020). Alberts et al showed that with age, vestibular information is down-weighted, whereas visual weight is increased and that this shift in sensory reweighting is primarily due to an age-related increase in the noise of vestibular signals (Alberts et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Visual dependence was calculated as the mean of the absolute values of the rod tilt from each trial of dynamic SVV minus the static SVV trials. Other studies also used a similar measure of VD with computerized (Cousins et al, 2014;Ulozienė et al, 2020) and noncomputerized versions (Roberts et al, 2016;Bednarczuk et al, 2020) of SVV.…”
Section: Methodsmentioning
confidence: 99%
“…In the process of sensory integration for spatial orientation, retinal information is highly accurate in detecting orientation of a visual stimulus while other sensory inputs are inherently noisier (Vandenbussche et al 1986 ; Tarnutzer et al 2009 ). Thus, visual cues can have a great influence on one’s perception of spatial orientation, and the extent of such reliance can be affected by other sensory information in both health and disease (Bronstein 1995 ; Cousins et al 2014 ; Roberts et al 2016 ; Bednarczuk et al 2020 ). For example, with changes in the head tilt position, where vestibular inputs become less reliable, visual cues usually have stronger influence on SVV responses (e.g., a static tilt of the visual background or visual motion) (Dichgans et al 1974 ; Young et al 1975 ; Vingerhoets et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…After competition of this condition, a third set of ten trials were then completed with the same spheres rotating at the same velocity but in the counterclockwise (CCW) direction. The use of rotating background on SVV has been widely used to study the effect of visual stimulation upon spatial orientation and verticality perception (Dichgans et al 1974 ; Cheung et al 1990 ; Cousins et al 2014 ; Roberts et al 2016 ; Bednarczuk et al 2020 ; Ulozienė et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%